First Characterization and Zoonotic Potential of Cryptosporidium spp. and Giardia duodenalis in Pigs in Hubei Province of China - Li, Dongfang; Deng, Han; Zheng, Yaxin; Zhang, Hongyan; Wang, Sen; He, Lan; Zhao, Junlong (Frontiers in Cellular and Infection Microbiology, 2022)
The zoonotic protozoa parasites Cryptosporidium spp. and Giardia duodenalis infect a wide range of hosts, including humans. Pigs are reservoir hosts for Cryptosporidium spp. and G. duodenalis, which can transmit cryptosporidiosis and giardiasis to humans and other animals. The current study sought to investigate the infection rates and species/genotypes of Cryptosporidium spp. and G. duodenalis in pigs in Hubei of China. The nested PCR and sequence analyses of the small ribosomal subunit RNA (SSU rRNA) gene for Cryptosporidium spp. and the β-giardin (bg) gene for G. duodenalis was utilized to screen for the infection of those parasites in a total of 826 fresh fecal samples. Both Cryptosporidium spp. and G. duodenalis infection rates were 0.97% (8/826). Of the genotyped positive isolates, 6/8 (75%) were C. scrofarum and 2/8 (25%) were C. suis, while two zoonotic species G. duodenalis assemblage E and assemblage A were also detected in 7/8 (87.5%) isolates and 1/8 (12.5%) isolates, respectively. The findings suggest that both of those parasites in pig in intensive farms of Hubei province, China, pose a potential public health risk.